Dampak Gaya Kepemimpinan Demokratis dan Komunikasi Internal terhadap Kinerja Karyawan - Muawanah; Bahri, Anjas Sasana (Idarotuna : Journal of Administrative Science, 2025)
Human resources play a crucial role in the success of an organization as they significantly impact employee performance. This study aims to examine the effect of democratic leadership style and internal communication on employee performance at CV. Bee Jay Seafoods in Probolinggo. Utilizing a quantitative approach, this research analyzes the impact of democratic leadership style and internal communication on employee performance, involving 104 employees as respondents. The results of data analysis show that both democratic leadership style and internal communication have a significant positive impact on employee performance. The partial hypothesis testing (t-test) indicates that both democratic leadership style and internal communication positively and significantly affect employee performance. This study contributes to understanding how leadership style and effective communication contribute to enhanced employee performance in the seafood processing industry. Additionally, it provides practical insights for improving management practices and fostering a productive work environment. The findings offer valuable implications for organizations seeking to optimize their workforce performance through improved leadership and communication strategies.